How to Conceptualize and Implement a PhD Program in Health Sciences—The Basel Approach. (23rd April 2018) - Keller, Franziska; Dhaini, Suzanne; Briel, Matthias; Henrichs, Sina; Höchsmann, Christoph; Kalbermatten, Daniel; Künzli, Nino; Mollet, Annette; Puelacher, Christian; Schmidt-Trucksäss, Arno; von Niederhäusern, Belinda; De Geest, Sabina
Objectives: Over the past decade, several excellent guidelines have been published on how to enhance the quality of PhD education in Europe. Aimed primarily at preparing students for innovative roles in their fields, they include variously structured approaches to curricular offerings, as well as other program components applicable across specialties (eg: supervisor support, scientific conduct, transferable skills). Since 2012, the interdisciplinary PhD Program in Health Sciences (PPHS) at the Faculty of Medicine of the University of Basel in Switzerland has focused on translating these guidelines into a 21st-century health sciences PhD program. Results: The PPHS started in 2012 based on the European Union (EU) guidelines for PhD education. This article describes the resulting interdisciplinary PhD program's conceptual underpinnings, rationale, structures, and 10 building blocks, like student portfolios, thematic training, interdisciplinary research seminars, student-initiated interdisciplinary activities, financial support of course participation, top-up and extension stipends, PhD supervision, research integrity, alumni follow-up network, and promotional tools including a dedicated website. Students enter from Clinical Research, Medicine Development, Nursing Science, Epidemiology and Public Health including Insurance Medicine, Sport Science (all from the Faculty of Medicine), and Epidemiology (Faculty of Science). Discussion and Conclusion: The Basel PPHS exemplifies state-of-the-art PhD education in Health Sciences based on European guidelines and offers guidance to other groups from conceptualization to rollout of an interdisciplinary health sciences PhD program.